METHODOLOGY OF TAFSIR AL-MUNIR WRITTEN BY AG. H. DAUD ISMAIL - Rifain, Aswar; Khalid, M. Rusydi; Haddade, Hasyim; Tahir, Muhyiddin (Jurnal Diskursus Islam, 2021)
This article elaborates the tafsir methodology used by local scholars, namely AG. Daud Ismail. This research is descriptive-analytic, which describes comprehensively the methodology of Tafsir al-Munir written by AG. H. Daud Ismail, which includes manhaj, sources, and ṭariqah (method). This research's primary and secondary sources are literature, which dominantly focuses on textbook research, especially Tafsir al-Munir in Buginese language written by AG. H. Daud Ismail. The results showed that Tafsir al-Munir used the tahlili methodology by explaining the relationship (munasabah) between verses or between one chapter and another. Explaining the causes of the descent (asbab al-nuzul), Analyzing vocabulary (mufradat) and the point of view of Arabic pronunciation from, Describing the general content of the verse, Explaining the fasahah elements, bayan and i'jaz, Explaining the laws that can be drawn from the discussed verse, Explaining the meaning and purpose contained on the verse which interpreted in fiqh style.